Read it and Weep: How Metaphor Limits Views of Literacy - Novek, Eleanor M. (Discourse & Society, 1992)
In the United States, as in most societies, the concept of literacy has as much to do with status and power relations as with the text-based skills of reading and writing. Because social relationships are constructed through language, the metaphors we use to talk about literacy help construct our views of it, but the conceptual shorthand they provide is problematic. This paper argues that metaphors found in public and scholarly discourse about literacy exaggerate the importance of certain concepts (notably the perceived powerlessness or deficiency of the non-reader) and ignore significant others, particularly the socioeconomic and political factors which dictate literacy `standards' and influence achieved levels of textual fluency. This work explores the implications of common literacy metaphors, tracing their entailments in the promotional materials of literacy programs, the popular press, scholarly articles and in the words of adult learners. It concludes that such metaphors may have significant negative effects on the ways we look at literacy, by obscuring the economic, social and political factors that constrain people from learning how to read and write, and by identifying literacy (or the perceived lack of it) as a personal attribute rather than as a social construction.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTkyMDAzMDAyMDA1